Not All Landscape Palm Fertilizers Are Created Equal - Timothy K. Broschat (EDIS, 2015)
Palms are widely planted in Florida landscapes. Their bold leaf textures create a tropical or Mediterranean look that is highly desired by residents and tourists alike. But palms have very high nutritional requirements, and deficiencies of any element can result in conspicuous and unattractive symptoms on their large leaves. UF/IFAS research shows that the most effective fertilizer has 100% of the N, K, Mg, and B sources in slow-release or controlled-release form and that all of the Mn, Fe, Zn, and Cu sources should be water soluble. This 4-page fact sheet explains the reasons for this recommendation and how to ensure that you have a formulation that will be effective. Written by Timothy K. Broschat, and published by the UF Department of Environmental Horticulture, April 2015. (Photo Credit: T.K. Broschat)